Biocompatibility of orthodontic adhesives in rat subcutaneous tissue - Rogério Lacerda dos Santos; Matheus Melo Pithon; Alline Birra Nolasco Fernandes; Márcia Grillo Cabral; Antônio Carlos de Oliveira Ruellas (University of São Paulo, 2010)
ABSTRACT OBJECTIVE: The objective of the present study was to verify the hypothesis that no difference in biocompatibility exists between different orthodontic adhesives. MATERIAL AND METHODS: Thirty male Wistar rats were used in this study and divided into five groups (n=6): Group 1 (control, distilled water), Group 2 (Concise), Group 3 (Xeno III), Group 4 (Transbond XT), and Group 5 (Transbond plus Self-Etching Primer). Two cavities were performed in the subcutaneous dorsum of each animal to place a polyvinyl sponge soaked with 2 drops of the respective adhesive in each surgical loci. Two animals of each group were sacrificed after 7, 15, and 30 days, and their tissues were analyzed by using an optical microscope. RESULTS: At day 7, Groups 3 (Transbond XT) and 4 (Xeno III) showed intense mono- and polymorphonuclear inflammatory infiltrate with no differences between them, whereas Groups 1 (control) and 2 (Concise) showed moderate mononuclear inflammatory infiltrate. At day 15, severe inflammation was observed in Group 3 (Transbond XT) compared to other groups. At day 30, the same group showed a more expressive mononuclear inflammatory infiltrate compared to other groups. CONCLUSION: Among the orthodontic adhesive analyzed, it may be concluded that Transbond XT exhibited the worst biocompatibility. However, one cannot interpret the specificity of the data generated in vivo animal models as a human response.